A pharmacopsychometric overview of major depressive episodes in positive psychiatry. (30th January 2018) - Bech, P.
ABSTRACT: Background: The use of the pharmacopsychometric triangle to enhance patient-reported well-being as the ultimate goal of treatment has most intensively been studied in patients with a major depressive episode. Methods: The review is structured on the pharmacopsychometric triangle in which the desired clinical effect of an antidepressive medication is balanced against the undesired side effects induced by this medication in terms of restored well-being. As a biological treatment, the antidepressive medication is compared clinically with both electroconvulsive therapy and psychological treatment. Results: In the process of this review, evidence from a dose–response study in patients suffering from a major depressive episode with an adequate duration and symptom severity has demonstrated that the dose–response relationship emerged when using the patient-reported well-being outcome rather than the symptomatic reduction as outcome. Conclusion: The pharmacopsychometric triangle is in patients with major depressive episodes providing important information within positive psychiatry.